The Linguistic Construction of Resilience and Power: A Discourse Analysis of Kamala Harris’s 2024 Post-Election Speech - Maria Fiani Daiman; Steffie Mega Mahardhika (INDO PUBLISHING, 2026)
This study examines how language constructs resilience, sustains authority, and conveys ideological meaning in Kamala Harris’s post-election speech following the 2024 United States presidential election. Using a qualitative approach within the framework of Critical Discourse Analysis, this study analyzes the official transcript to identify recurring linguistic patterns and their discursive roles. It addresses the limited attention given to post-election speeches in discourse analysis, particularly in understanding how meaning and authority are negotiated after electoral outcomes. The findings show that the speech systematically employs personal pronouns, modal verbs, repetition, and metaphorical expressions to shape meaning, engage audiences, and position the speaker within a broader political context. These linguistic choices function as discourse strategies that transform an unfavorable electoral outcome into a narrative of continuity and future engagement. The speech also reflects democratic values, collective resilience, and inclusive leadership in political discourse.